"Efecto de tres niveles de proteina en la alimentacion de la vieja azul (Aequidens rivulatus) en la etapa juvenil". - Fabara Bermúdez, Yeltsin Iván (2018)
In order to study the effects of the protein in the feeding of old blue, this work was done, 150 specimens of old blue juveniles were used, which had a weight of 30g, three groups were randomly selected of 50 fish which were distributed in 15 cages of a pool of 15x40x0.80m, the fish were fed manually to visual satiety (ad libitum) for 8 weeks 3 times a day with commercially balanced PRONACA of 32, 38 and 50% protein , every week he took the weight of the fish. A completely randomized design (DCA) with 3 treatments and 5 repetitions was applied to determine the difference of the means, the TUKEY multiple range test was used. In the variable weight, there was no statistically significant difference between the three treatments, with the exception of the third, fourth and fifth weight, where the best treatment was 50% protein; In variables such as length and height there is no statistically significant difference between treatments. Based on the results obtained, it is concluded that in the variables where I present statistical differences, the best was the food that contained 50% protein. . Keywords: Feeding, weight, protein, old blue